Day 1 Wed, April 18, 2018 2018
DOI: 10.2118/191318-ms
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Silica Nanoparticles in CO2-Foam for EOR and CCUS at Tough Reservoir Conditions

Abstract: We show experimentally that surface treated silica nanoparticles greatly enhance the thermodynamic stability of CO2-foam compared to other foam stabilizers at elevated temperatures and salinities in the presence of oil. The aqueous nanofluid mixes with CO2 in the porous media to generate CO2-foam for enhanced oil recovery by improved sweep efficiency, resulting in reduced carbon footprint from oil production. Our results show that surface modified nanoparticles are able to stabilize CO2-foam at elevated temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 112 publications
(131 reference statements)
0
2
0
Order By: Relevance
“…Nanoparticles have been investigated to stabilize foam by many researchers Ibrahim et al 2017;San et al 2017;Nazari et al 2018;Razali et al 2018;Rognmo et al 2018).…”
Section: Recent Research Reviewmentioning
confidence: 99%
“…Nanoparticles have been investigated to stabilize foam by many researchers Ibrahim et al 2017;San et al 2017;Nazari et al 2018;Razali et al 2018;Rognmo et al 2018).…”
Section: Recent Research Reviewmentioning
confidence: 99%
“…Chen et al reported that the cationic surfactant ethoxylate alkyl amine is a good foaming agent for carbonate reservoir and can be used at high temperature (120 °C) and high salinity (up to 180,000 ppm) conditions. Many nonionic surfactants are applicable in moderate temperature and salinity because of low cloud points, at which head groups of nonionic surfactants tend to dehydrate and precipitate. , Rognmo et al , investigated CO 2 -foam enhanced oil recovery (EOR) in carbonate reservoirs, as well as its potential for CO 2 storage using a nonionic surfactant. Chen et al reported that a highly ethoxylated nonionic surfactant can generate stable foam at 111 °C with 30 g/L NaCl.…”
Section: Introductionmentioning
confidence: 99%